A JUXTAPOSE EXAMINATION OF EXPERIENCES AMONG TRANSFER STUDENTS IN UNITED STATES AND CURRENT STUDENTS IN MALAYSIA - Bessie Ong; Kok Choy Cheong, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
An American Degree Transfer Program (ADP) represents one of the options for Malaysian students who wish to obtain a degree from Universities in the United States (US). However, ADP students who eventually transfer often lack on-the-ground information about the study experience in US. This could lead to mismatched expectations on learning experiences that might affect academic performance. This paper explores experiences that might potentially impact the adjustment of transfer students in US and compares similar experiences with students currently enrolled in ADP. Both groups of participants answered a self-administered survey questionnaire that enquires their perceptions on a variety of factors that could contribute to positive learning experiences. The findings revealed that class environment, academic rigor, assessment model, interactions with faculties and socio-cultural issues were some of the dimensions reported by students that impact experiences in both US and Malaysian universities. Except for assessment model, there were differences in experiences between US campuses and ADP in the other dimensions. Academic trouble, defined as transfer shock, was evident only among the Engineering students due to the difficulty level of courses in this discipline. The results from this study provide an insight for potential students planning to transfer to US to realign their expectations with reality.